P021 Vitamin D receptor-dependent protective effect of moderate hypoxia in a mouse colitis model Running title: Hypoxia prevents mouse colitis through VDR. (21st January 2022) - Wang, Z; Hong, Y; Hong, L; Changzhi, H; Jiaming, Q
Abstract: Background: Although physiological hypoxia is important for maintaining the intestinal barrier, its effect on the barrier during acute colitis and the underlying mechanisms are not fully understood. Here, we aim to explore the influence of hypoxia in dextran sulfate sodium (DSS)-induced colitis mice and the role of hypoxia-inducible factor (HIF) and vitamin D receptor (VDR) in the process Methods: Colitis mice were subjected to hypoxia to detect colitis symptoms and intestinal barrier function changes. Finally, the mechanisms underlying the changes were explored in a colon cell line. Results: First, compared with colitis mice without hypoxia stimulation, those with hypoxia stimulation showed significantly decreased pathological damage and improved permeability of the intestinal barrier. The expression of tight junction proteins (including occludin, claudin-1 and ZO-1), HIF-1α as well as VDR was up-regulated in colitis mice with hypoxia stimulation. However, in VDR gene knockout (VDR-KO) colitis mice, hypoxia treatment showed no protective effect, suggesting the VDR dependency of this effect. Second, we identified that although hypoxia stimulation could enhance the single-layer epithelial transmembrane electrical resistance in DLD-1 cells, these effects disappeared in VDR-knockdown cells. Furthermore, over-expression of HIF-1α in DLD-1 can increase the expression of VDR, then chromatin immunoprecipitation and luciferase assays confirmed that HIF-1α can bind to the promoter region of the VDR gene under hypoxia. Finally, compared with their wild-type siblings, VDR-KO mice showed reduced abundance of anaerobic bacteria and SCFA-producing bacteria. Conclusion: Moderate hypoxia was protective against DSS-induced colitis, and VDR is instrumental in it. Furthermore, HIF-1α mediates the effect of hypoxia on the VDR signaling pathway. Moreover, intestinal flora may be an important link between hypoxia and VDR.